Sa liyab ng libong sulo - Ilagan, Bonifacio P. ([s.l.] Labor Education and Assistance for Development and AsiaVisions Media Foundation, 1997)
A video collage depicting Philippine history and revolution, from the pre-Spanish era to the Ramos administration.
VHS.
Ang "Liyab ng libong sulo" ay humango ng inspirasyon sa "Lipunan at rebolusyong Pilipino" ni Amado Guerrero.
Keywords: Philippine history